Plan Estratégico de Marketing para la Comercialización de Panela Pulverizada Producida en el Municipio de Chitaraque Boyacá en el Mercado Español - Angarita Montaña, Andrés Felipe (Universidad Antonio Nariño, 2021)
This project aims to capture and identify the different aspects that perfectly understand the different key activities to carry out the marketing plan for powdered panela to the Spanish market, since for them powdered panela is an ideal substitute for sugar, It is much more economical, and it is intended to enter this market, with a strategy from the point of view of marketing, which includes the price, the promotion, place, and a strong point and of great importance the product since it is intended to adapt the product with an ecological package, and with an organic content, but that in turn all these processes are low cost.